FACTORS AFFECTING LABOR PRODUCTIVITY AT PT. TELKOM REGIONAL DIVISION VII (PERSERO) MAKASSAR CITY - Jam'an, Jam'an; A.M, Sanusi; Musa, Nursantiawati (Jurnal Ekonomi Balance, 2018)
This study aims to determine the factors of employee productivity at PT. Telkom Regional Division VII (Persero) Makassar City, in terms of education level, work experience and gender. Research data obtained from the method of presenting data from the results of respondents' responses (questionnaires), and this is secondary data from telecommunications companies at PT. Telkom Regional Division VII (Persero) Makassar City, the statistical factors used in this study were multiple regression analysis using the SPSS program. The findings of this study indicate that the factors of labor productivity at PT. Telkom Regional Division VII (Persero) Makassar City which consists of education level, work experience and gender simultaneously (together) have a significant effect on employee productivity at PT. Telkom Regional Division VII (Persero) Makassar City in 2017. This is evidenced by the results based on the results of the coefficient of determination R square, the result is 0.477. meaning that productivity factors together affect employee performance by 47.7%. the rest is influenced by other factors outside this research. Based on the results of the linear regression test, the unstandardized coefficient B value of the education level is 0.522, which is greater than the work experience of 0.322. and the smaller gender is 0.211 This means that 52.2%, employee performance is influenced by education level. From the results of this study it can be concluded that the factors are more dominant in increasing employee productivity.